Evaluasi Kinerja Keuangan: Kemandirian dan Pertumbuhan Pendapatan Asli Daerah - Budiharjo, Roy; Budiyastuti, Triyani; Wardoyo, Dwi Urip; Rahman, Asrarul (Gorontalo Accounting Journal, 2025)
This study aims to analyze the financial independence of Cilacap Regency during the 2019–2023 period, with a specific focus on the regional financial independence ratio and the growth of Locally-Generated Revenue (PAD). The approach used in this study is a quantitative method with ratio analysis techniques. The results indicate that the average financial independence ratio of Cilacap Regency only reached 26%, placing it in the low category. The fluctuations in PAD growth over the past five years also demonstrate notable dynamics, with an average growth rate of 20%. The financial relationship pattern between the Central Government and Cilacap Regency tends to be instructive, reflecting a high dependence on central government transfers. The implications of these findings highlight the importance of diversifying PAD sources, improving budget management efficiency, and optimizing local potential to enhance regional financial independence.